Using Narrative Films to Combat HIV-Related Stigma in Western Kenya: An Exploratory Pilot Study of Adolescents Living With HIV and Their Caregivers - Brittany M. McCoy MD; Carole I. McAteer MS; Celestine Ashimosi; Josephine Aluoch MS; C. Thomas Lewis MFA; Winstone Nyandiko MBChB, MMED, MPH; Rachel C. Vreeman MD, MS (SAGE Publishing, 2024)
Objective. Interventions that effectively address HIV-related stigma are urgently needed to improve outcomes for adolescents living with HIV (ALHIV). We piloted a series of 4 short narrative films depicting Kenyan ALHIV's lived experiences of stigma and discrimination with 57 ALHIV and 50 adult caregivers of ALHIV in western Kenya. Methods. Participants completed either pre- and post-viewing questionnaires, including an HIV/AIDS-related stigma and discrimination scale, or participated in post-viewing focus group discussions. Three-month follow-up visits were conducted. Results. Caregivers endorsed significantly greater disagreement with stigmatizing statements on the scale at 3-month follow-up, whereas adolescents had no significant differences in scores. Participants reported they believed the films would have a positive impact on their communities and had led to changes in their own attitudes, beliefs and/or behavior. Conclusion. The HIV Stigma Films may show promise as an intervention to reduce stigmatizing attitudes and beliefs about HIV-infection, especially among caregivers of ALHIV.